2014
DOI: 10.1186/scrt476
|View full text |Cite
|
Sign up to set email alerts
|

Motor neuron derivation from human embryonic and induced pluripotent stem cells: experimental approaches and clinical perspectives

Abstract: Motor neurons are cells located in specific areas of the central nervous system, such as brain cortex (upper motor neurons), brain stem, and spinal cord (lower motor neurons), which maintain control over voluntary actions. Motor neurons are affected primarily by a wide spectrum of neurological disorders, generally indicated as motor neuron diseases (MNDs): these disorders share symptoms related to muscular atrophy and paralysis leading to death. No effective treatments are currently available. Stem cell-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 59 publications
(114 reference statements)
2
33
1
Order By: Relevance
“…Our studies demonstrated that the BVVL-MNs showed a significant reduction in their axonal length, improved by riboflavin treatment. This phenotype is similar to that observed in MN disease such as SMA203031, and this neuropathological feature could be responsible for BVVL neurological motor signs. In fact, several studies have demonstrated a reduction in axonal growth in the MNs derived from SMA-iPSCs relative to control iPSCs2032.…”
Section: Discussionsupporting
confidence: 81%
“…Our studies demonstrated that the BVVL-MNs showed a significant reduction in their axonal length, improved by riboflavin treatment. This phenotype is similar to that observed in MN disease such as SMA203031, and this neuropathological feature could be responsible for BVVL neurological motor signs. In fact, several studies have demonstrated a reduction in axonal growth in the MNs derived from SMA-iPSCs relative to control iPSCs2032.…”
Section: Discussionsupporting
confidence: 81%
“…Yet, they remain at present the best model for the evaluation of some ALS-related mechanistic processes in living ALS patients and in asymptomatic ALS gene mutation carriers. The utilization of fibroblast-derived induced pluripotent stem cells reprogrammed to motor neurons from either ALS patients or asymptomatic mutation carriers [36,40,41] may help in the near future to disclose specific neurodegenerative pathways in asymptomatic mutation carriers. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as it has been shown that iPS cells can be generated from human dermal fibroblasts [117,118] and many groups are capitalizing on this chance to produce embryonic-like iPS cells from patients with MN disease such as ALS [119][120][121][122]. Thus, the clinical potential of patientderived iPS lies in the ability for patient-specific disease modeling, high-throughput drug screening, and perhaps eventually gene editing and cell replacement therapy [122,123].…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%